Bank Lending and Interest Rate Changes in a Dynamic Matching Model - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 1998)
This paper presents theory and evidence on the dynamic relationship between aggregate bank lending and interest rate changes. Theoretically, it proposes and solves a stochastic matching model where credit expansion and contraction are time consuming. It shows that the response of bank lending to changes in money market rates is likely to be asymmetric and depends crucially on two structural parameters: the speed at which new loans become available, and the speed at which banks recall existing loans. Empirically, it provides evidence that bank lending in Mexico and the United States responds asymmetrically to positive and negative shocks in money market rates.